Transformasi pemikiran pembaharuan dan modenisme di Malaysia: satu penelitian awal - Kamarudin Salleh, (Universiti Kebangsaan Malaysia, 2012)
This article is an initial study relating to the thought of renewing and modernism in Malaysia which undergoing the process of transformation since the beginning of the twentieth century till nowadays. This type of thought can be ascertained through the rise of individuals and organizations that uphold such stand, ideas and ideologies. This study basically presents the proper and concise understanding of the concept Islamic modernism such as characteristics, form, nature, development and history. Modernism then, examined specifically in the Malay Archipelago and Malaysia through the political thought of UMNO and PAS that struggle for the Malays and Islam. The results show that both of the political parties tried to accommodate the notion of modernism in practical and real context that influencing much by the political purposes and struggles.